2011
DOI: 10.1182/blood-2011-05-353920
|View full text |Cite
|
Sign up to set email alerts
|

Digestive vacuoles of Plasmodium falciparum are selectively phagocytosed by and impair killing function of polymorphonuclear leukocytes

Abstract: Sequestration of parasitized erythrocytes and dysregulation of the coagulation and complement system are hallmarks of severe Plasmodium falciparum malaria. A link between these events emerged through the discovery that the parasite digestive vacuole (DV), which is released together with infective merozoites into the bloodstream, dually activates the intrinsic clotting and alternative complement pathway. Complement attack occurs exclusively on the membrane of the DVs, and the question followed whether DVs might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 57 publications
1
56
0
Order By: Relevance
“…1b). We have reported that the activating particles become coated with C3 and C5b-9 [14,18]. Now, the striking finding was made that focal deposits of C3 also became detectable on the bystander RBCs (Fig.…”
Section: Deposition Of Activated C3 On Bystander Erythrocytesmentioning
confidence: 86%
See 2 more Smart Citations
“…1b). We have reported that the activating particles become coated with C3 and C5b-9 [14,18]. Now, the striking finding was made that focal deposits of C3 also became detectable on the bystander RBCs (Fig.…”
Section: Deposition Of Activated C3 On Bystander Erythrocytesmentioning
confidence: 86%
“…DVs were isolated, enumerated and banked in 50 % glycerol at −20 °C as described [14,18]. Immediately prior to use, they were washed twice in veronal-buffered saline (VBS) (Virion/Serion, Würzburg, Germany) and, unless otherwise stated, employed at a 1:1 ratio with target cells.…”
Section: Parasite Culturementioning
confidence: 99%
See 1 more Smart Citation
“…In bloodstage infection, schizont rupture releases merozoites and digestive vacuoles leading to immune system exposure. A recent study has found digestive vacuoles serve as major complement activation targets with MAC forming on their surface (36)(37)(38). Intriguingly, these studies did not observe terminal pathway formation on merozoites, a strong indication that complement evasion strategies are in place to protect this cell type from complement-mediated attack.…”
mentioning
confidence: 87%
“…17,18 We reported recently that when parasitized erythrocytes rupture in blood, the DVs are rapidly phagocytosed by polymorphonuclear granulocytes (PMNs). 19 Phagocytosis only occurred in active serum and complement factor C3 was found attached to the surface of the organelle. It followed that the DV might directly activate complement, so experiments were performed to explore this possibility, leading to the novel findings reported herein.…”
Section: Introductionmentioning
confidence: 99%